Evidence for variability time-scale-dependent UV/X-ray delay in Seyfert 1 AGN NGC 7469. Issue 3 (21st April 2020) - Pahari, Mayukh; McHardy, I M; Vincentelli, Federico; Cackett, Edward; Peterson, Bradley M; Goad, Mike; Gültekin, Kayhan; Horne, Keith
ABSTRACT: Using a month-long X-ray light curve from RXTE /PCA and 1.5 month-long UV continuum light curves from IUE spectra in 1220–1970 Å, we performed a detailed time-lag study of the Seyfert 1 galaxy NGC 7469. Our cross-correlation analysis confirms previous results showing that the X-rays are delayed relative to the UV continuum at 1315 Å by 3.49 ± 0.22 d, which is possibly caused by either propagating fluctuation or variable Comptonization. However, if variations slower than 5 d are removed from the X-ray light curve, the UV variations then lag behind the X-ray variations by 0.37 ± 0.14 d, consistent with reprocessing of the X-rays by a surrounding accretion disc. A very similar reverberation delay is observed between Swift /XRT X-ray and Swift /UVOT UVW 2, U light curves. Continuum light curves extracted from the Swift /GRISM spectra show delays with respect to X-rays consistent with reverberation. Separating the UV continuum variations faster and slower than 5 d, the slow variations at 1825 Å lag those at 1315 Å by 0.29 ± 0.06 d, while the fast variations are coincident (0.04 ± 0.12 d). The UV/optical continuum reverberation lag from IUE, Swift, and other optical telescopes at different wavelengths are consistent with the relationship: τ ∝ λ 4/3, predicted for the standard accretion disc theory while the best-fitting X-ray delay from RXTE and Swift /XRT shows a negative X-ray offset of ∼0.38 d from the standard disc delay prediction.